(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Innovation in digital marketing in the midst of a pandemic. There has been a meteoric rise in the use of generic marketing materials since COVID-19. In the wake of this pandemic scenario, many marketers have rethought their strategies for connecting with consumers and expanding their businesses. After the COVID-19 pandemic, it became clear that the digital marketing procedure had an effect on certain MSME. This paper’s literature evaluation focuses on the role of digital marketing as a foundational aspect of company growth. As a means to further corporate improvement, it imposes a culture and methodology on service expansion. Incorporating the following design and philosophical aspects into the study’s methodological approach allowed it to achieve all of its aims. The most crucial part of the COVID-19 predicament is the impact of digital marketing on the bottom lines of certain companies and what this means for the digital transformation strategy.